(untitled) (Annual of the Faculty of Philosophy in Skopje, 2010)
Cognitive Behavioral approach is focused to the difficulties that client has “now and here” at it is based of developing a common point of view of the client’s problem. Cognitive Behavioral approach is used with individuals, families and groups of people for giving psychosocial help and support to everyone no matter of the people abilities, culture, gender or sexual preference. Psychotherapists that gain this model are professionals in mental health, like medical nurses, psychologists, doctors, social workers and counselors. Cognitive behavioral approach can be used in group or individually, only the therapy or in combination with medicaments depending from the client’s problem. The main steps in the structure of this approach are identifying negative thoughts, modifying negative thoughts, identifying and modifying dysfunctional assumptions and behavioral experiment.